1997
DOI: 10.1111/j.1440-1746.1997.tb00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for Helicobacter pylori infection in a multi‐racial dyspeptic Malaysian population undergoing endoscopy

Abstract: The aim of the present study was to determine the risk factors for Helicobacter pylori in a dyspeptic Malaysian population. A cross-sectional survey of 1060 consecutive patients presenting with dyspepsia at the Endoscopic Unit, University Hospital, Kuala Lumpur, Malaysia from January 1994 to July 1995 was undertaken. All patients answered a detailed questionnaire and underwent endoscopy, with two antral biopsies taken for diagnosis of H. pylori using a rapid urease test. An overall H. pylori prevalence of 49.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 7 publications
(1 reference statement)
3
57
2
1
Order By: Relevance
“…H. pylori infection can be related to low levels of sanitation, hygiene, education. [8][9][10] In this study, no relationship was observed between education status and H. pylori infection. However, further studies are needed, especially in poor socioeconomic and rural areas.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…H. pylori infection can be related to low levels of sanitation, hygiene, education. [8][9][10] In this study, no relationship was observed between education status and H. pylori infection. However, further studies are needed, especially in poor socioeconomic and rural areas.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been reported that the prevalence of H. pylori infection was related to several of these factors, including socioeconomic status, crowded living conditions, low levels of hygiene, age, geographical region, ethnic group, cigarette and alcohol consumption. [8][9][10] Also, prevalence of H. pylori infection differs both between and within countries. 11,12 Although in the Iranian population the prevalence has been reported to range from 57 to 91%, [13][14][15][16][17] …”
Section: Introductionmentioning
confidence: 99%
“…In a seroprevalence study from Singapore, a significant linear correlation was found for Chinese and Malay subjects but not for Indians (18). We have previously noted this paradox with peptic ulcer disease where a larger proportion of H. pylori-positive Indian patients had nonulcer dyspepsia compared to Chinese and Malays (19). The lower frequency of GCA among Indians despite the high H. pylori prevalence can indeed be termed the "Indian enigma" and suggests the influence and interaction with other, probably protective factors.…”
Section: Discussionmentioning
confidence: 77%
“…H. pylori infection is common in China (61%), Taiwan (54%), Korea (69%), and Malaysia (49%), the countries of origin for the participants in this study. [5][6][7][8] The evidence that H. pylori infection increases a person's risk for gastric cancer is convincing. A large prospective study followed over 1,000 Japanese patients who underwent esophagogastroduodenoscopy (EGD) for various reasons, and found that only patients infected with H. pylori went on to develop gastric cancer.…”
mentioning
confidence: 99%